Perbedaan Kepercayaan Diri Remaja Putri Pengguna dan Non-Pengguna Ortodonti Cekat Berdasarkan Indeks PIDAQ - Nurkhansa Putri, Aisyah; Nofrizal, Riko (Jurnal Kedokteran Gigi Terpadu, 2025)
Background: The self-confidence of adolescent girls is frequently influenced by their physical appearance, particularly the aesthetic condition of their teeth. Consequently, fixed orthodontic treatment may contribute to enhancing their self-esteem. Objectives: To examine the difference in self-confidence levels between adolescent girls who have undergone fixed orthodontic treatment and those who have not undergone fixed orthodontic treatment at SMA Negeri 42 Jakarta. Methods: A comparative analytical observational study with a cross-sectional design was conducted, involving 70 female students. The participants were divided into two groups: those who had undergone fixed orthodontic treatment for a minimum duration of one year and those who had not. Self-esteem was evaluated using the PIDAQ questionnaire, focusing on the DSC component. Data analysis was carried out using univariate and bivariate statistical methods with SPSS. Results: The statistical analysis revealed a significant difference between the two groups (p < 0.05), suggesting that fixed orthodontic treatment positively influences adolescent girls' self-confidence with regard to dental aesthetics. Conclusion: Female students who have undergone fixed orthodontic treatment show different self-confidence levels than students who have not, based on the PIDAQ index.